Revitalizing Heavily Worn Teeth: A Detailed Case Report of Full Mouth Rehabilitation - N Vishesh; Basavaraj S Salagundi; B L Bhavana; S Pavithra (Journal of Multidisciplinary Dental Research)
The management of tooth wear, especially attrition, is becoming a subject of increasing interest in the prosthodontic literature, both from a preventive and a restorative point of view. Dealing with patients who have worn dentition is intricate and challenging. Precise clinical and radiographic assessments, along with a diagnostic wax-up and OVD determination, are pivotal in managing this condition. A crucial element involves establishing the occlusal vertical dimension (OVD) using a systematic method, resulting in a reliable treatment outlook. In this case report attrited teeth were restored with metal-ceramic restorations and a removable partial denture was fabricated for maxillary and mandibular edentulous areas. An occlusal splint was used to protect the restorations. The treatment protocol yielded a pleasing aesthetic and functional outcome. This result can encourage clinicians to seek accurate diagnosis and treatment planning to treat such patients. Keywords Full mouth rehabilitation, Occlusal vertical dimension, Prosthetic dentistry, Prosthodontics, Tooth wear, Worn dentition